ROLE OF MICRORNA AND POLYMORPHISMS OF FOXP3 AND ADRB2 GENES IN PATHOGENESIS OF PULMONARY DISEASES - Bersimbaev, R.I.; Akparova, A.Yu.; Aripova, A.A.; Kausbekova, A.Zh. (Academic Journal of Physical and Chemical Sciences, 2018)
The study of the key mechanisms of the development of bronchopulmonary diseases as asthma and chronic obstructive pulmonary disease (COPD) and asthma and chronic obstructive pulmonary disease overlap syndrome (ACOS) are the current directions of molecular medicine. Genetic predisposition as well as influence of environmental factors play an important role in the development of asthma and COPD which are multifactorial diseases. Epigenetic mechanisms also affect regulation of gene expression during asthma, COPD and ACOS. The epigenetic regulation includes methylation of DNA, microRNA, histone modifications and they are all induced by influence of environmental factors. Higher levels of methylation of FOXP3 and ADRB2 DNA are at a higher risk of asthma development. However, there is not enough evidence on the level of methylation of the FOXP3 and ADRB2 genes and microRNA in patients with COPD and ACOS. It should be noted that the epigenetic labels established during the study of cancer and autoimmune disorders have shown their value as biomarkers of diagnosis. In this case, the study of genetic and epigenetic mechanisms of asthma, COPD and ACOS is a relevant objective of biomedicine because it helps to explain the interaction between genes and environmental factors in order to develop diagnosis and personalized treatment for the patients with bronchopulmonary diseases